2013
DOI: 10.3109/10715762.2013.842979
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum arginase I with L-arginine, 3-nitrotyrosine, and exhaled nitric oxide in healthy Japanese workers

Abstract: The associations of serum arginase I with serum L-arginine, serum 3-nitrotyrosine, and fractional exhaled nitric oxide (FENO) were evaluated cross-sectionally in healthy Japanese workers. The serum median (minimum-maximum) levels of arginase I, 3-nitrotyrosine, and FENO in healthy people (n = 130) were 14.6 (0.94-108.1) ng/mL, 81.0 (0.27-298.6) pmol/mg protein, and 14.0 (5.0-110.0) parts per billion, respectively. Significant correlations of arginase I with FENO, L-arginine, 3-nitrotyrosine, and percent predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Social support was positively associated with arginase I. Previously, we showed a high serum level of arginase I in asthma and the correlation of arginase I with hs-CRP [30], as well as the association of arginase I with oxidative stress [17, 18]. Oxidative stress is associated with depression [3134].…”
Section: Discussionmentioning
confidence: 99%
“…Social support was positively associated with arginase I. Previously, we showed a high serum level of arginase I in asthma and the correlation of arginase I with hs-CRP [30], as well as the association of arginase I with oxidative stress [17, 18]. Oxidative stress is associated with depression [3134].…”
Section: Discussionmentioning
confidence: 99%
“…No correlation was found between arginase activity and L-arginine in healthy controls or asthmatic patients [14]. We previously demonstrated that arginase I was negatively associated with L-arginine and 3-nitrotyrosine in healthy individuals [15]. Decreases in L-arginine levels by arginase I may contribute to the generation of 3-nitrotyrosine, an oxidative stress biomarker, due to the uncoupling of NOS.…”
Section: Discussionmentioning
confidence: 95%
“…In a healthy population, we found a relationship between serum arginase I and serum L-arginine [15]. After liver transplantation, an inconsistency was noted in the reduction of L-arginine by the release of arginase [16,17].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations